The puzzle of architecture and bureaucracy - Agarez, R. C.; Floré, F.; Devos, R. (Architectural History, 2022)
Architecture and bureaucracy: indissociable and irreconcilable? The two spheres are often seen in opposition — the latter curtailing the former’s creative power — yet might they not also overlap, partake and occasionally coincide in their processes? Dismissing the role of bureaucracy in architecture as extraneous or detrimental seems to hinder our capacity, as thinkers and producers of architecture, to work through this relationship and explore ways of dealing with a pervasive tool of contemporary societal organisation; whereas understanding the fraught relationship might help us bridge the gap that, in many contexts, separates architecture and the communities it exists to serve. This special collection explores how architecture and bureaucracy have negotiated their stances in the twentieth century. In particular, it aims to shed light on instances where knowledge of architecture was an element in, and a product of, the machinery of bureaucracy. Beyond the notion of bureaucracy in architecture as a site of imposition and control — and the vivid sentiments of frustration and deception it prompts — lies a terrain where less contrasted, more fine-grained actions and exchanges occur. The ways in which these two spheres relate are diverse and merit scholarly attention, as the articles that follow demonstrate.